SOVEREIGNTY OUTSIDE THE SYSTEM: THE EXAMPLE OF AFGHANISTAN AND THE CRISIS OF INTERNATIONAL NORMS - Ahmadaliyev A'zamjon Abdusattor o'g''li (Modern American Journals, 2026)
Since 2021 Afghanistan has represented a paradoxical case in contemporary international relations. The country demonstrates stable territorial control, a functioning administrative apparatus, and a consolidated monopoly on the use of force, while remaining outside the framework of formal international recognition. This article examines whether sovereignty can exist beyond institutionalized international order and argues that the Afghan case reflects a broader structural crisis of international norms rather than an isolated anomaly. Drawing on empirical observations and normative analysis, the article conceptualizes sovereignty as a set of practices rather than a legal status, highlighting the growing gap between formal recognition and effective governance. Afghanistan is presented as an indicator of the transformation of the international system, where pragmatic interaction increasingly substitutes for normative coherence.
Keywords: Sovereignty, non-recognition, international norms, Afghanistan, de facto governance